Claudin 6 Is a Positive Marker for Atypical Teratoid/Rhabdoid Tumors - Birks, Diane K. (Brain Pathol, 2009)
Atypical teratoid/rhabdoid tumors (AT/RTs) are highly aggressive pediatric brain tumors characterized by the presence of rhabdoid cells and negative immunostaining for INI1 (BAF47). Histogenesis is unknown and diagnosis can be challenging because of their extreme morphological and immunophenotypic heterogeneity. Currently no signature markers other than INI1 loss have been identified. To search for possible candidate proteins of interest in AT/RTs, Affymetrix GeneChip® microarrays were utilized to investigate nine AT/RTs vs. 124 other tumor samples. The most distinctive gene identified was claudin 6 (CLDN6), a key component of tight junctions. CLDN6 showed moderate or higher mRNA expression in eight of nine AT/RTs, with little to no expression in 114 of 115 other tumors. Average expression was 38‐fold higher in AT/RTs vs. other samples. Immunohistochemical (IHC) staining of 33 tumor specimens found positive membrane staining in seven of seven AT/RTs, and was negative in 26 of 27 other brain tumor samples. Notably, none of the 16 medulloblastomas/primitive neuroectodermal tumors showed IHC staining for CLDN6. IHC staining results closely matched the level of mRNA expression detected by microarray. CLDN6 may be a useful positive marker to help further identify AT/RTs for diagnostic and treatment purposes.